ANALISIS IMPLEMENTASI STRATEGI PADA PERUSAHAAN ES BATU CV. DUMPI AGUNG LAMONGAN - SE, Sumantri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study looked at the perspective of leadership and organizational structure that support the strategic implementation then used that two elements to analyze it, to know how far the achievement of company goals. The type of research has been used is descriptive qualitative research. The object in this study is CV. Dumpi Agung Lamongan. The results showed that in terms of leadership, managers have a clear vision that agreed with the owner's vision of the company and accepted by the employee. Managers must also provide direction, incorporate all elements within the company and become role models, can motivate all employees,  and  be  able to  achieve  sales  goals  and  order  from  consumers. However, the  application  of  leadership  on  this  company  has obstacle.  This obstacle occur due to lack of communication and inter–functional coordination in the top management level. In terms of organizational culture, the company builds a culture of "Work Discipline, Timely, Delivering the Best Product, and Excellent Service for Consumers". This organizational culture plays a role in supporting the company's main strategy today, which is to improve product quality to raise the selling price of the product. The culture is well–organized by company employees through good managerial oversight. The relationship of leaders and employees manifested through discussion at the stalls during lunch break, pursuing the same hobby, and present in the same study.Keywords: Strategic Implementation, Leadership, Organization Culture